Clinical profile and outcome of the patients with spontaneous duodenal perforation and their association with H. pylori infection - Najar, Rownaq R.; Shah, Mubashir A.; Naqash, Sameer H. (International Surgery Journal, 2021)
Background: Peptic ulcer disease is highly prevalent in general population managed mainly by medical treatment with H2 blockers, proton pump inhibitors and antibiotics with eradication of Helicobacter pylori, the complications have reduced, but perforation is still frequently occurring and is always a surgical emergency. Methods: It was a hospital based retrospective observational study from January 2015 to June 2017 and prospective observational study from July 2017 to June 2019. Study patients were diagnosed, managed and operated for perforated peptic ulcer at Sheri-i-Kashmir Institute of Medical Sciences, Soura, Kashmir, India. Data of 44 patients was collected using a standard proforma and their risk factors, operative procedure, post-operative progress and outcome was analysed. Results: In our study of 44 cases, patients between ages of 21-30 years (31.8) were commonly affected and there was male predominance (95.5%). Smoking, use of NSAIDS and improper treatment for peptic ulcer were major risk factors. 61.4% patients presented within 24 hours of presentation. Cellan Jones repair was performed in 60.4% patients. Complications were due to co-morbid illness, age and delayed presentation for treatment. Conclusions: Perforated peptic ulcer (PPU) is a frequent surgical emergency in our state, predominantly affecting young aged male, may be because of dietary habits (very spicy food), smoking, NSAIDS and other risk factors. Surgical intervention is always warranted. Simple closure with omental patch is standard procedure, followed by treatment for H. pylori eradication and was effective and majority of patients survived despite delayed preoperative admission.